Factors Affecting Service Per Conception of Ongole Cross-breed Cattles in Tanjung Sari District - Kunaifi Wicaksana; Dani Nur Arifin (JURNAL ILMIAH PETERNAKAN TERPADU, 2021)
One of the parameters to see the reproductive performance of cattle is service per conception (S/C). The lack of information on important factors affecting S/C in Ongole Cross-breed (PO) cattles breeding underlies this research. The analysis in this research was linear regression using the MINITAB 16 application. The results of the research for service per conception (S/C) in Ongole Cross-breed (PO) cattles in Tanjung Sari sub-district were classified as ideal with a value of 1.29 ± 0.52. Each increase in the value of the BCS score will increase the S/C value. Each added age value at first married, it will increase the S/C value. Each added value of the parent's age will reduce the S/C value. The conclusion in this study is that S/C in PO cattles in Tanjung Sari District is 1.29 ± 0.52. Factors that affect the value of conception rate in PO cattles in Tanjung Sari district was the BCS score which was positively associated with S/C with a value of 0.553, age at first mated was negatively associated with S/C with a value of -0.434, and age parent was negatively associated with S/C with value of -0,114.